Genetic disorders on the island of Mauritius - Wallis, Colin E (Division of Human Genetics, 2017)
Inherited disorders are an important cause of physical handicap, deafness, mental retardation and blindness. There is considerable variation in the geographic and ethnic distribution of genetic disease due to biological pressures and historical accidents. In this context the relative prevalence of common inherited disorders and the recognition of rare conditions in isolated communities is of great academic importance. Oceanic islands are of special significance in the study of inherited disease. Virtually nothing has been documented concerning genetic disorders on the Island of Mauritius with a population of one million people. This study was undertaken to document the impact of inherited disorders on handicapping conditions in this community. As genetic disease concentrates in institutions, formal screening of all the schools for the deaf and blind, and the associations for the physically and mentally handicapped on Mauritius was undertaken. This involved a careful history, clinical examination and genealogical study, with radiographic, biochemical and ancillary testing performed where appropriate. Referral clinics were also established for the assessment of individuals and families known, or thought to be afflicted with abnormalities or handicap of a genetic origin. To ensure completeness, a similar survey was performed on Rodrigues, a neighbouring island, as this community is included under the responsibilities of the Mauritian Ministry of Health. Accumulated data concerning 681 patients were analysed. Genetic disorders accounted for disability in 265 individuals representing 38,6% of the causes of handicap. Of these persons 54 were deaf, 30 were blind, 99 were mentally retarded and 80 were physically handicapped. Several new entities, considered unique to the area and a consequence of either consanguinity or the founder effect, were documented. Karyotyping on selected individuals was undertaken in the laboratories of the Department of Human Genetics, University of Cape Town. A molecular genetic study of a large family with X-linked deafness of Nance, conducted by the same laboratory, revealed tight linkage with the probe pDP34; linkage analysis was performed on patients with Duchenne muscular dystrophy. The collation of these original data, the delineation of the new genetic conditions and an analysis of the results form the subject of this thesis and provide a basis for the future development of genetic services on Mauritius.